THE EFFECT USING PICTURE SERIES TECHNIQUE ON STUDENTS’ WRITING NARRATIVE TEXT - Faridatul HS. (Graduate Program, University of Islam Malang, 2020)
The objectives of the research are: (1) Do the students who taught by using picture series have better achievement in writing narrative text than those who are not taught by using picture series technique writing for the eighth grade students of MTs Zainul Hasan IV in the academic year 2019/2020.The lookup was once carried out at MTs Zainul Hasan IV East Java, from October 2019. The lookup approach was once experimental. The matters of the lookup are the college students of the eighth grade A and the second grade B. Each of them consists of 20 students. There are 5 boys and 15 females in the eighth grade A and there are moreover 9 boys and eleven females in the eighth grade B. The eight grade A is as an experimental class which used to be taught the utilization of picture series and the eighth grade B is as a control class which used to be taught using translation. The facts have been obtained from test. The researcher acquired quantitative statistics for her research. They are the students’ rankings of students’ writing take a seem at after having eight instances treatment for each and every class. The researcher analyzed the facts the use of ANOVA by means of the use of SPSS 20.The result analysis test used descriptive statistic, normality test, test of paired pattern t test, homogeneity test, test of impartial sample t test. The descriptive statistic was pretest of experimental group is 16.90 and imply for pretest of control team is 16.35. The researcher found imply of experimental of posttest is 20.80 and imply control group of posttests is 18.70. Standard Deviation for pretest of experimental group is 1.804. And Standard Deviation for pretest of control group.is 1.089. A normality test used to be 0.097, while 0.097>0.05 (a: 5%), it should be referred to that the facts used in this research have been usually distributed. test of paired sample t test was each of the corporations have been the equal at (2-tailed) at Sig 0 lower than 0.05. But from the skill of experience -3.900 used to be greater than -2.350 of the.control group homogeneity test was once the posttest used to be 0.268 > 0.05. It should be said that the variance of the posttest information was homogeneous test of independent pattern t test was the sig (2-tailed) used to be < 0.05, it should be concluded that statistically exceptional or significant on the probability. And the mean distinction was 2.100, because it has high quality value it capability that the first group of experimental group was higher than the 2d group or control group.Keywords: Picture Series, Narrative Text, Writing Skill.